The Missing Link in Intercultural Competence Development: The University’s Organizational Capability to Deliver - Gregersen-Hermans, Jeanine (International Higher Education, 2014)
Internationalization is an established reality at most continental European universities, with intercultural competence development as one of its traditional rationales. The problem is that there is little clarity on how higher education institutions have progressed in this regard. The organizational capability to deliver forms a missing link; constraints can be observed at the level of the institution, the academic discipline and the individual academic. A university wide change program focusing on intercultural competence development seems needed.